Revision Facelift and Neck Lift - Dibbs, Rami P.; Chamata, Edward; Ferry, Andrew M.; Friedman, Jeffrey D. (Seminars in Plastic Surgery, 2021)
Facial rejuvenation procedures have become more commonly performed due to an increasing elderly population and greater general public acceptance. As a result, patients are now increasingly undergoing secondary and tertiary rhytidectomies to treat natural aging and/or to correct complications from prior procedures. Revision face and neck lifts are more complex by nature of the procedure and require a comprehensive preoperative assessment for enhanced outcomes. In this review, we discuss the preoperative evaluation, surgical challenges encountered, primary face and neck lift deformities, and their surgical management for patients undergoing secondary face and neck lifts.
Keywords: rhytidectomy; neck lift; revision; secondary procedure